2016
DOI: 10.1007/978-3-319-27228-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Treatment Studies on Free Water Surface Constructed Wetland System

Abstract: Scarcity of safe drinking water is a major problem faced by mankind in recent years. Because of increase in population and over exploitation of natural water resources, fresh water resources are declining day by day. Considering the above scenario, protection of the available limited fresh water resources from deterioration in quality deserves utmost importance. This study aims to evaluate the wastewater treatment efficiency of a constructed wetland system using a laboratory scale model of the wetland system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Constructed wetlands predominantly consist of a sedimentation basin and a macrophyte zone containing media and vegetation. As urban stormwater flows through the sedimentation basin and the macrophyte zones, pollutants are removed through physical (e.g., sedimentation and filtration), chemical and biological (e.g., root zone uptake and microbial degradation) processes (Vymazal 2005;Midhun et al 2016). Previous studies have demonstrated the high removal rates of heavy metals from urban stormwater, with average removal rates of 57, 65, 65 and 52% for Cd, Cu, Pb and Zn, respectively (Birch et al 2004;Lucas et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Constructed wetlands predominantly consist of a sedimentation basin and a macrophyte zone containing media and vegetation. As urban stormwater flows through the sedimentation basin and the macrophyte zones, pollutants are removed through physical (e.g., sedimentation and filtration), chemical and biological (e.g., root zone uptake and microbial degradation) processes (Vymazal 2005;Midhun et al 2016). Previous studies have demonstrated the high removal rates of heavy metals from urban stormwater, with average removal rates of 57, 65, 65 and 52% for Cd, Cu, Pb and Zn, respectively (Birch et al 2004;Lucas et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect use of untreated wastewater is one of the most common and extensive types of unintentional wastewater reuse [4][5][6][7][8]; this occurs when untreated wastewater is discharged into freshwater streams, gets diluted and subsequently used by farmers, households and industries. This is a common practice in low-and middleincome countries without or with limited collecting and treatment capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In Kerala, India, a CW system using a laboratory scale model with the common wetland plant 'Reed' showed removal efficiencies for domestic wastewater treatment of 87. 36, 57.93, 83.7, 86.6, 36.66, 98.28, and 61.83 % Water Environment Research, Volume 89, Number 10 -Copyright © 2017 Water Environment Federation respectively for total dissolved solids (TDS), dissolved oxygen (DO), biochemical oxygen demand (BOD5), chemical oxygen demand (COD), Total Kjeldahl Nitrogen (TKN), nitrate, and sulphate respectively (Midhun et al, 2016). Similarly, a low cost laboratory scale integrated constructed wetland (ICW) system planted with native species, Veronica anagallis-aquatica sp., was compared with a non-vegetative species at various detention times, and it was found that the vegetated ICW showed higher removal efficiency over non-vegetated system: 69.12% vs.…”
mentioning
confidence: 99%